The Role of LSP P3 Junior SPA Therapist Competency Certification on Work Readiness and Absorption of the Tourism Industry - Nawanksari, Septiari; Sudira, Putu; Mutohhari, Farid (Universitas Pendidikan Ganesha, 2021)
The fundamental problem in business is the low readiness of occupational therapists as experts. In addition, the low job readiness of therapists is exacerbated by the low absorption of prospective therapists. LSP P3 competency certification is an essential program for improving spa therapists' work readiness and labour absorption in the tourism industry. This study aims to analyze how much influence the competence of the LSP P3 Junior Spa certification on Asesi's work readiness and Asesi's absorption in the spa tourism industry. Ex-post facto research with a quantitative approach. A total of 66 respondents of spa therapist assessment were included in this study as a sample. Data were collected through a questionnaire with a 4 Likert scale questionnaire instrument. Data analysis was performed using regression analysis and SEM analysis. The results showed that the LSP P3 Junior Spa Therapist competency certification had a significant effect on Asesi's work readiness and Asesi's absorption in the tourism industry in the spa sector. The certification program must improve the quality of its implementation. Educational and training institutions must organize various competency certification programs that are even more optimal, especially when competency testing must be carried out in-depth material by the perceptions of the spa therapist workforce.